JAMINAN KEPASTIAN HUKUM YANG TERKANDUNG DALAM SERTIPIKAT HAK ATAS TANAH - Ramadhani, Rahmat (DE LEGA LATA: JURNAL ILMU HUKUM, 2017)
The product of the land registration process is a certificate of title granted to the right holder. The certificate according to Government Regulation No. 24 of 1997 is in the form of one sheet of documents containing information about the juridical data and physical data required on a parcel of registered land. Although the certificate of land rights is referred to as the strongest evidence but in reality the certificate of land rights has not fully guaranteed legal certainty. This is because the law still opens loopholes for other legal subjects to question it both personally and in groups within the judiciary. In order to ensure legal certainty of a right to land for the right holder, the certificate of land rights must be tested in three aspects: relating to; Legal Certainty of Object, Legal Certainty of Status of Rights and Legal Certainty on Subject.